Synthesis of 5‐Alkyl‐ and 5‐Phenylamino‐Substituted Azothiazole Dyes with Solvatochromic and DNA‐Binding Properties - Pithan, Phil M. (Chemistry, 2019)
A series of new 5‐mono‐ and 5,5′‐bisamino‐substituted azothiazole derivatives was synthesized from the readily available diethyl azothiazole‐4,4′‐dicarboxylate. This reaction most likely comprises an initial Michael‐type addition by the respective primary alkyl and aromatic amines at the carbon atom C5 of the substrate. Subsequently, the resulting intermediates are readily oxidized by molecular oxygen to afford the amino‐substituted azothiazole derivatives. The latter exhibit remarkably red‐shifted absorption bands (λ (abs)=507–661 nm) with high molar extinction coefficients and show a strong positive solvatochromism. As revealed by spectrometric titrations and circular and linear dichroism studies, the water‐soluble, bis‐(dimethylaminopropylamino)‐substituted azo dye associates with duplex DNA by formation of aggregates along the phosphate backbone at high ligand–DNA ratios (LDR) and by intercalation at low LDR, which also leads to a significant increase of the otherwise low emission intensity at 671 nm.